Globalisation and the labour market: an analysis of job stability and job security in Britain - Prajapati, Bina (2011)
Globalisation represents the increased international integration of goods, services, labour, technology, knowledge, ideas and capital of national economics from around the world. It also evokes many opinions in relation to the costs and benefits it can provide. Globalisation can bring greater benefits to countries in the form of greater productivity and output, potentially faster economic growth, increased welfare and even greater incentives to innovate. However, workers fear that globalisation costs more jobs than it creates (Eurobarometer, 69) and it could cause the structure of employment to permanently change over time. Ideally, workers would like to have jobs that last a life time Gob security) and jobs that pay a predictable wage Gob stability). Yet, should workers become dislocated from their jobs through firm closure or through layoffs, workers hope their prospective re-employment in new jobs is secure and stable with few short-term adjustment costs over time. But, many workers believe 'jobs are not for life' and this is in part attributed towards globalisation - increased trade and advancements in technology, the fall in transportation costs, exchange rate volatility and offshoring are all potential factors that have contributed towards greater competition in world markets for goods and services over the last thirty years. This thesis examines whether job security and job stability have changed over this time. It focuses on whether offshoring and the advancements in technology have increasing made jobs less secure and whether they have increasing made wage levels within jobs more volatile.